THEODOSIUS DOBZHANSKY AND THE EVOLUTION OF HUMANITY: A DIFFERENT APPROACH (Annual of the Faculty of Philosophy in Skopje, 2024)
The text is a plausible presentation and critical review of the main work ofTheodosius Dobzhansky: “Evolution of Humanity”. It tries to show and proves thatDobzhansky tries and largely succeeds in offering a different, let’s say, dialectical interpretationof the biological evolution of humanity, i.e., the stages and differences inthe evolution of the human species and race. Following in the footsteps of, but also incontrast to, traditional Darwinism and some similar evolutionary theories, Dobzhanskyinsists on the claim that evolution, primarily biological, is not over, but that it is stillgoing on, despite human, i.e., a cultural intervention, namely simultaneous and together/conjunctive with it, which seeks to influence and change the directions of the existingnatural flows and processes. During the multi-millennium history, biology and culturebecame interdependent and interfering, with which man (woman and man) with hisappearance asserted himself as the main and most responsible factor/agent of the fateof the human race and the survival of the human community/human species, namelysurvival of oneself, but also of the totality and entirety of the planetary biodiversity, asa necessary prerequisite for one’s own survival and existence.In his research on the evolution of humanity, Dobzhansky starts from the inspiringviews of some famous predecessors, such as Pierre Teilhard De Chardin, but wecan argue that Dobzhansky influenced many of his contemporaries, including NoamChomsky, especially when it comes to linguistic research on the genesis and emergenceof human language, and the influence of transformative-generative grammar on thedevelopment of the human mind, i.e., on the development of the human brain.At the same time, we can state that Dobzhansky’s research and insights correspondand coincide with the research and ethical attitudes of some modern bioethicists,philosophers of biology and culturologists, as well as with the attitudes of manylike-minded people and followers.
Keywords: evolution; biology; culture; language; human; humanity